2011
DOI: 10.4236/fns.2011.27103
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Fungi and Mycotoxins in Some Commercial Baby Foods in North Africa

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
(28 reference statements)
2
7
0
Order By: Relevance
“…Aspergillus and Penicillium were the prevalent genera contaminating baby foods, and these results were in agreement with refs . which found that Aspergillus , Penicillium , Fusarium , Mucor , Cladosporium and Rhizopus were the commonest genera contaminating baby foods.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Aspergillus and Penicillium were the prevalent genera contaminating baby foods, and these results were in agreement with refs . which found that Aspergillus , Penicillium , Fusarium , Mucor , Cladosporium and Rhizopus were the commonest genera contaminating baby foods.…”
Section: Resultssupporting
confidence: 92%
“…Infants eat these weaning foods until 24 months . Carbohydrates and proteins are the main components of baby foods, as they are manufactured from cereals (wheat, sorghum, rice, maize, millet and oats), milk, leguminous foods/grains, fruits and nuts so they are appropriate medium for microbial contamination …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diseases due to the consumption of contaminated food with mycotoxins and molds are known worldwide. Grain and milk products are the most sensitive ones to contamination with mycotoxins among foods [71]. In mycotoxicosis cases, consumption of animal products (milk and dairy products, meat and meat products, egg, liver, kidney) has a major role as well as consumption of grain and grain products.…”
Section: Fungal Contaminants and Mycotoxins In Conventional Animal Prmentioning
confidence: 99%
“…Even when fungi contamination and variety is high mycotoxin can form less. According to a research in infant foods aflatoxin was detected only in 2.4% (19-70 μg/kg) of specimens despite of high fungus contamination [71]. In the European Union and some other countries accepted limits of AFM1 varies for raw milk is between 0.05 and 10 μg/kg, for dairy products is between 0.02 and 10 μg/kg [70].…”
Section: Fungal Contaminants and Mycotoxins In Conventional Animal Prmentioning
confidence: 99%